Land Consultant Enterprise / Mohd Noor Ishak and Muhmmad Nuzmin Yaapar - Ishak, Mohd Noor; Yaapar, Muhammad Nuzmin (2002)
Land Consultant Enterprise type of business that we are making now giving a service about planning and designing the landscape. The government of Perlis is now encouraging its citizens to plant as much of trees since the weather here is warm and need trees to reduce it. One of his statements saying that he wanted to make the area of Kangar as a district in the garden. Location of our business at Taman Sena Indah, 01000 Kangar, Perlis Indera Kayangan. Our business will start on first of January 2005 .